Ataxia induced by small amounts of alcohol. Issue 3 (1st September 1998) - Setta, F; Jacquy, J; Hildebrand, J; Manto, M-U
Abstract : A patient is described who exhibited cerebellar ataxia after drinking small amounts of alcohol. Intake of 5 g alcohol induced a gaze evoked nystagmus, a scanning speech, a body sway after eye closure, and bilateral postural leg tremor. Kinematic and EMG analysis of fast wrist movements showed normal movements before and marked hypermetria after alcohol intake. Dysmetria was due to abnormal programming of antagonist muscle activity.